Determinants of the Adoption of Integrated Reports: An International Investigation - Md. Jahidur Rahman; Pan Li; Rashedul Hasan (Universitas Pasundan, 2020)
This study examines the determinants of companies’ reporting decisions. We employ three measures at the country-level: (1) investor protection, (2) trade union density, and (3) economic development. Regression model analysis was used to measure whether companies used integrated reports (IR) or traditional sustainable reports. Using sample data from Fortune Global 300 for the year 2017, which is the latest available data, this paper follows logistic regression models. The study finds out that the probabilities of publication of IR are high in countries with high trade union density, weak investor protection, and low levels of economic development. These results help companies and managers to better cope with current business environments.